Secondary amine-functionalised metal–organic frameworks: direct syntheses versus tandem post-synthetic modifications. Issue 30 (28th June 2016) - Keenan, Luke L.; Hamzah, Harina Amer; Mahon, Mary F.; Warren, Mark R.; Burrows, Andrew D.
Abstract : We compare two routes to prepare functionalised MOFs and show that direct synthesis with a functionalised dicarboxylic acid is better for zinc MOFs whereas post-synthetic modification is better for chromium MOFs. Abstract : [Zn4 O(bdc-NH2 )3 ], IRMOF-3 (bdc-NH2 = 2-amino-1, 4-benzenedicarboxylate), and [Cr3 O(H2 O)2 F(bdc-NH2 )3 ], MIL-101(Cr)-NH2, undergo tandem post-synthetic modification reactions with aldehydes and NaCNBH3 to form secondary amine-functionalised metal–organic frameworks (MOFs). The degree of conversion ranges from 17–74% for IRMOF-3 (2a–i ) and from 35–51% for MIL-101(Cr)-NH2 (4a–d ), and alkene, sulfide, ferrocenyl and pyridyl substituents can be successfully introduced into the zinc MOFs. For both the zinc and chromium MOFs, an increase in the steric bulk of the aldehyde leads to a reduction in the degree of conversion. Low conversion with bulky aldehydes can be exploited to generate products containing two different secondary amine substituents, such as [Zn4 O(bdc-NH2 )1.93 (bdc-NHCH2 CH2 CH2 SMe)0.47 (bdc-NHEt)0.59 ]2k in which sequential tandem modifications have taken place. N2 adsorption experiments reveal that the post-synthetically modified MOFs display lower than anticipated BET surface areas together with hysteresis. This is consistent with some degradation of crystallinity occuring on treatment with NaCNBH3, as verified by control experiments, which leads to the formation of mesopores. Reactions of H2 bdc-NH2 with aldehydes and NaCNBH3 afforded a series of secondary amine functionalised dicarboxylic acids H2 L 1–8 after acid work up. These acids were reacted with Zn(NO3 )2 ·6H2 O to form the secondary amine-functionalised MOFs5a–h through direct synthesis. 1 H NMR analysis of5a–g showed the presence of some bdc-NH2 linkers in addition to the secondary amine-containing linkers, and indeed the presence of H2 bdc-NH2 was required for the reaction with H2 bdc-NHCH2 Fc (Fc = ferrocenyl) to form a crystalline MOF. In the case of the zinc MOFs, N2 adsorption experiments generally showed greater BET surface areas for the products of the direct synthesis reactions than for those from post-synthetic modifications suggesting that, in this case, the former is the best approach to these functionalised MOFs. In contrast, post-synthetic modification is the optimal approach to form crystalline derivatives of MIL-101(Cr)-NH2 as direct synthesis gave amorphous products.